Challenges affecting the Effective Implementation of Community-Oriented Policing in Abuja Municipal Area Council, Nigeria - Elizabeth, Owonibi Ola; Ukawilulu, J. O. (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
This article examines the challenges affecting the implementation of community-oriented policing in Abuja Municipal Area Council, Nigeria. Over the years policing in Abuja has been confronted with problems like increased crime, terrorism and general insecurity. Despite, the adoption of community-oriented policing in April 27 th , 2004 which was a welcomed strategy to deal with the crime trend, yet the crime is still on the increased. Community-oriented policing as a strategy is a proactive philosophy that promotes problem-solving, and problem oriented policing in tackling the crime and insecurity that affect the quality of life, and citizens fear of crime. It entails identifying, analysing and addressing the community problems at their roots. It also involves partnership between the police and members of public as co-producers of safe community. The method employed was survey; multi-stage sampling was used, while questionnaire and oral interview were used as instruments of data collection for 400 respondents.  The study revealed that, community-oriented policing implementation in Nigeria is faced with series of challenges. These include misconception of the core value of community-oriented policing, police-public perceptions, and inadequate fund from the government, inadequacy equipment and technology to support services, corruption, and so on. The study recommends that it is pertinent for all the stakeholders to have a proper training in order to understand the concept of community-oriented policing for effective delivery of the strategy in the reduction of crime and fear of crime, for safety and security in Abuja Municipal Area Council. Keywords: Challenges, Community policing, Crime prevention, partnership, safety, security, strategy.